A MODELLING FRAMEWORK FOR RAILWAY INFRASTRUCTURE RELIABILITY ANALYSIS - Fourie, Cornelius Jacobus; Zhuwaki, Nigel Tatenda (The South African Journal of Industrial Engineering, 2017)
The maintenance and management of railway infrastructure plays a central role in ensuring the reliability and availability of rail transport. In a highly competitive transport market, the rail industry is required to employ new and innovative maintenance strategies that will position rail transport as an affordable and reliable transportation alternative. This can be realised through implementing maintenance strategies that prioritise efficient resource allocation. Application of reliability-based techniques to make informed decisions in maintenance management, with an overall aim of reducing operational expenditure while maintaining safety and efficiency, has been increasing. This paper presents a framework for the application of a reliability-based technique to evaluate the reliability of railway infrastructure systems.